Factors which influence trust in supply chains. Issue 1 (2nd January 2018) - Ruel, Salomée; Shaaban, Sabry; Wu, Junhao
ABSTRACT: As economic globalisation continues, developing inter-organisational collaboration between firms has become an inevitable trend. Collaboration is seen as being necessary for firms to survive in their markets since it can provide supply chain partners with many advantages related to new product launches, new market penetration and innovation. The literature shows that trust is an important part of the collaboration concept. By analysing a sample of questionnaire responses, this paper investigates the influence on trust in supply chains of seven factors and five basic company information items. The results show that all seven of the studied factors correlate both with trust and among themselves with a very high significance level. However, of the five basic information items, only market share has a significant effect on trust.